PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TYPE MAKE A MATCH UNTUK MENINGKATKAN HASIL BELAJAR IPS SEJARAH SISWA KELAS VII C SMPN I KOTO KAMPAR HULU - Nursalina '; Isjoni '; Kamaruddin ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstrak: The problem in this research is that students do not understand the explanation given by the teacher, because the teacher teaching only give lectures, so that students are not motivated to learn and ignore the student activity. To improve learning outcomes IPS History class VII C Senior High School 1 Koto Kampar Hulu through the Cooperative Model Type Make A Match. This research was held on 7 April to 21 April 2016yang done as much as two cycles. Subjects in this study were students of class VII C amounting to 23 students who serve as a source of data. Data collection instrument in this essay is to test students' achievements and activity observation sheet teachers and students. In this thesis presented student learning outcomes through the final test results cycle I and II. The improvement that occurred in the first cycle with an average daily quiz 66.30% and 80.65% second cycle. Learning outcome is supported by the increased activity of the teachers and students. In the first cycle of increased activity of teachers by 80% to 95%. While improving student activity increased from 75% to 92.5%. From the research results obtained show that the students managed to increase IPS History with good learning outcomes so that the implementation of cooperative models Type Make A Match in this study is proven and can be accepted in improving learning outcomes IPS History class VII C Senior High School 1 Koto Kampar Hulu.Keywords: Cooperative Model Type Make A Match, IPS Learning Outcomes History.